A new species of Amphimedon (Porifera, Demospongiae, Haplosclerida, Niphatidae) from the Capricorn-Bunker Group of Islands, Great Barrier Reef, Australia: target species for the sponge genome project - Hooper, John N.a.; van Soest, Rob W.m. (Zootaxa, 2006)
A new niphatid demosponge, Amphimedon queenslandica sp.nov., is described from Heron and One Tree Islands, southern Great Barrier Reef, Queensland, Australia. The new species is of particular significance as it is currently the subject of the first sponge genome project. The species is characterized within the globally distributed genus Amphimedon by its distinctive blue-green colour, and the combination of encrusting-lobate growth form, spongin-rich spiculofibres and feeble spicule size, The new species is compared and contrasted with known or suspected Amphimedon species of Australia and adjacent territories of Papua New Guinea, New Caledonia and Indonesia.